2001
DOI: 10.1002/lsm.1039
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of infarct size in rats and dogs after myocardial infarction by low‐energy laser irradiation

Abstract: The results of the present study indicate that delivery of low-energy laser irradiation to infarcted myocardium in rats and dogs has a profound effect on the infarct size after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 26 publications
(33 reference statements)
5
95
0
2
Order By: Relevance
“…Photobiomodulation by light in the red to near-IR range (630-1,000 nm) using low-energy lasers or light-emitting diode (LED) arrays has been shown to accelerate wound healing, improve recovery from ischemic injury in the heart, and attenuate degeneration in the injured optic nerve (19)(20)(21)(22)(23)(24). At the cellular level, photoirradiation at low fluences can generate significant biological effects, including cellular proliferation, collagen synthesis, and the release of growth factors from cells (22,25,26).…”
mentioning
confidence: 99%
“…Photobiomodulation by light in the red to near-IR range (630-1,000 nm) using low-energy lasers or light-emitting diode (LED) arrays has been shown to accelerate wound healing, improve recovery from ischemic injury in the heart, and attenuate degeneration in the injured optic nerve (19)(20)(21)(22)(23)(24). At the cellular level, photoirradiation at low fluences can generate significant biological effects, including cellular proliferation, collagen synthesis, and the release of growth factors from cells (22,25,26).…”
mentioning
confidence: 99%
“…Our results confirm the positive bio-stimulatory effect of LLLT, which depends mainly on the ability of the tissue to respond to light energy. The mechanisms underlying stimulation of bone healing may be multifactorial and include: promotion of angiogenesis [26], collagen production [27], osteogenic cell proliferation and differentiation [28]. Another study in the tibia of rats stated that the improvement of bone repair by LLLT was due to its role in upregulation of cyclooxygenase-2 expression in bone cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have cited possible inhibitory effects caused by LLLT (32)(33)(34), and it is not uncommon to find authors who correlated the Arndt-Schulz law with inhibitory or paradoxical responses (35)(36)(37)(38)(39). This law was introduced in the late 19th century by H Schulz, who used potentially harmful chemicals in small doses and observed that they promoted biostimulator effects (39,40).…”
Section: Discussionmentioning
confidence: 99%